Design, Fabrication and Performance of Wind Turbines 2020 - Kim, Kyung Chun (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
From small-scale vertical axis wind turbines for urban usage to large-scale horizontal axis wind turbines for offshore wind farms, design, fabrication, and optimization technologies are highly required to manage wind energy effectively. Moreover, some new opportunities, such as in wind farm design, fluid-structure interaction, aero-acoustics, fabrication methods and performance tests by experimental and computational fluid dynamics should be engaged in modern wind turbine communities. The basic objectives of this book include improving the reliability and promoting the high efficiency of wind turbines as well as their dynamic performance, reducing wind turbine-generated noise and improving power generation efficiencies through high-fidelity approaches. Students, scholars, and engineers who manage such a wide range of wind turbine scales and usages, design, fabrication, and performance test protocols for various wind turbines, are highly recommended to read this book.